2012
DOI: 10.1016/j.bmc.2011.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Multi-receptor drug design: Haloperidol as a scaffold for the design and synthesis of atypical antipsychotic agents

Abstract: Using haloperidol as a scaffold, new agents were designed to investigate the structural contributions of various groups to binding at CNS receptors associated with atypical antipsychotic pharmacology. It is clear that each pharmacophoric group, the butyrophenone, the piperidine and the 4-chlorophenyl moieties contributes to changes in binding to the receptors of interest. This strategy has resulted in the identification of several new agents, compounds 16, 18, 19, 23, 24 and 25, with binding profiles which sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 19 publications
1
39
0
Order By: Relevance
“…It was also observed that replacement of the carbonyl functional group in haloperidol with an oxygen or a sulfur atom retains D 2 binding and increases affinity at the 5-HT 1A receptor, indicating that the carbonyl group is not essential for binding at the D 2 R but can be replaced with other groups to produce compounds that bind with high affinity to the receptors associated with antipsychotic properties. 8 …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It was also observed that replacement of the carbonyl functional group in haloperidol with an oxygen or a sulfur atom retains D 2 binding and increases affinity at the 5-HT 1A receptor, indicating that the carbonyl group is not essential for binding at the D 2 R but can be replaced with other groups to produce compounds that bind with high affinity to the receptors associated with antipsychotic properties. 8 …”
mentioning
confidence: 99%
“…810 The alkylating agent, (3-chloropropyl)(4-fluorophenyl)sulfane, was prepared using the procedure in our previously published paper, 8 with slight modification, by refluxing 4-fluorobenzenethiol and 1-bromo-3-chloropropane in the presence of K 2 CO 3 in iPrOH. The other two alkylating agents were similarly prepared by using the corresponding n-fluorobenzenethiol.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2, 21, 22 In this article, we explored different modifications to pharmacophoric groups (Figure 1) present in ligands that have high affinity for CNS receptors or elaborated structurally similar functionalities to such pharmacophores. The working hypothesis was that by modifying the arylalkyl groups attached to the amino groups in the pharmacophores shown in Figure 1, it was possible to broaden the affinity of a target compound to other CNS receptors including the D 2 R, 5-HT 1A R, 5-HT 7 R and SERT.…”
Section: Introductionmentioning
confidence: 99%
“…Using the commercially available bis-boc-pyrazolocarboxamidine (AstaTech, Inc.; CAS No. : 862686-58-6) we synthesized the alcohol side chain, 23 and then installed it via a Mitsunobu reaction 27 to provide the di- N -boc pyrazole guanidine reagent (Scheme 4; R = H) as a suitable advanced intermediate envisioned for the synthesis of numerous analogs derived from anilines.…”
mentioning
confidence: 99%